An Executive Law Review of Paid Up Capital Regulations for Foreign Investment Limited Liability Companies as a Mechanism of Legal Protection for the Indonesian Public - Gede Amatya Ananta; Johanes Ibrahim Kosasih; Ni Luh Made Mahendrawati (JURNAL AKTA, 2026)
Foreign Direct Investment (FDI) through the establishment of Limited Liability Companies (PT PMA) plays a strategic role in driving national economic development. However, weak regulation and supervision of minimum paid-up capital requirements have triggered various legal issues, including fictitious capital injections, unfair business competition, and threats to public interests. This study aims to examine the effectiveness of paid-up capital regulations in PT PMA through an executive law review approach and to identify legal loopholes that allow regulatory deviations. The research adopts a normative juridical method with statutory, conceptual, and non-judicial case study approaches. The findings reveal fundamental weaknesses in the current regulatory framework, including the absence of independent verification mechanisms, overly permissive norms, and weak administrative sanctions. Accordingly, regulatory reform is necessary by introducing sector-based capital thresholds, mandatory external audits, and strengthening cross-sectoral supervision. Improved regulatory governance is expected to enhance legal protection for the public and ensure that foreign investment delivers tangible and sustainable contributions to the national economy.